Podcast Training for Students at MBI Amanatul Ummah Pacet Mojokerto - Puji Laksono; M. Alfin Fatikh; Achmad Damaio (Sahwahita: Community Engagement Journal, 2025)
This article provides an overview of the enormous potential for podcast development at MBI Amanatul Ummah, as seen from the extracurricular activities, many students are talented, especially in journalism. Many organizational activities are covered and broadcast through the school's social media. The use of foreign languages, such as Arabic and English, in students' daily lives also presents a unique potential for podcast development at this madrasah. Students are already accustomed to public speaking. This provides capital to develop student creativity through podcasts. The author's analysis of podcast development at MBI Amanatul Ummah requires student empowerment to adapt to current developments in the cyber society era. Empowerment refers to students' potential abilities. Based on the results of community service at MBI Amantul Ummah Pacet Mojokerto using the Asset-Based Community Development (ABCD) approach, the results of the community service 1) Implemented podcast training for students at MBI Amantul Ummah Pacet Mojokerto such as planning with topic determination, content plan, making podcast cover. Choosing a good topic in making a podcast, and a scenario in a contemporary content design that can attract a potential audience. Making a creative and innovative podcast cover. Opportunities for podcast development for schools and good communication techniques in making podcasts, such as public speaking, body language, good self-performance, choosing language in podcasts, and searching for literature as podcast material. 2) providing material related to equipment preparation in making podcasts, both hardware and software. Good recording or shooting techniques in making podcasts. The process of editing recorded podcast works and publication, such as choosing a hosting service, platform, and podcast promotion. As well as choosing a room, room management, and room interior in the podcast process.  Recommendations, 1) increase the participation of all academics of MBI Amanatul Ummah Pacet Mojokerto in developing podcasts as a school education media, 2) increase the participation of students who are members of intra-school and extracurricular organizations to actively participate in developing podcasts as a medium for student creativity at MBI Amanatul Ummah Pacet Mojokerto, 3) increase the participation of the Havara organization as the main organization in the field of journalism to become a driving force for podcast development at MBI Amanatul Ummah Pacet Mojokerto.